Effects of rhEPO on Nrf2 and HO-1 expression in rats with acute kidney injury and its protective effects on kidney - Zhang, Kunying; Sun, Wenkui; Wang, Zhanzhao; Ma, Wenming; Qin, Lili (Cellular and Molecular Biology, 2020)
If the kidney suddenly loses its ability to remove waste, acute kidney injury (AKI) will occur that dangerous levels of waste may accumulate, and the chemical composition of the blood may become unbalanced. AKI usually develops rapidly within a few days and is very common in hospitalized patients, especially those in urgent need of intensive care. AKI can be fatal and requires serious treatment. However, it can be reversible. The purpose of this research was to investigate the effects of recombinant human erythropoietin (rhEPO) on the expression of nuclear factor E2-related factor 2 (Nuclear factor E2, Nrf2) and Heme oxygenase (HO-1) in rats AKI and its protective effects on the kidney. For this purpose, 40 SD rats were averagely and randomly divided into 4 groups: control group, sham operation group, model group, and rhEPO group. The rhEPO group was injected with 5% glucose mixed with rhEPO to form 3000 IU/ (kg/d) rhEPO. Except for the rhEPO group, three groups were injected with 5% glucose at the same dose level as the rhEPO group respectively. Before the third administration, the renal pedicle was clamped for 60 min and then perfused for 24 hours. Changes of Serum creatinine (Scr) and Urea nitrogen (BUN) of rats in each group were detected before and after modeling. Twenty-four hours after modeling, renal tissues of rats in each group were taken, and expressions of Nrf2 and HO-1 in renal tissues were detected by qRT-PCR and Western blot methods. There were no significant differences in Scr and BUN contents in the four groups before modeling (p> 0.05). There were no significant differences in Scr and BUN contents in the control group and sham operation group after modeling compared with those before modeling (p> 0.05). Expressions of Nrf2 and HO-1 in the rhEPO group were higher than those in the model group, the sham operation group and the control group (p< 0.05), while expressions of Nrf2 and HO-1 in model group were higher than those in sham operation group and control group (p< 0.05). There were no significant differences in expressions of Nrf2 and HO-1 between the sham operation group and the control group (p> 0.05). rhEPO can induce expressions of Nrf2 and HO-1 in AKI rats. RhEPO has a protective effect on the kidney, which may be related to expressions of Nrf2 and HO-1.